Performance of Anatomically Designed Quadripolar Left Ventricular Leads: Results from the NAVIGATE X4 Clinical Trial. (19th August 2016) - MITTAL, SUNEET; NAIR, DEVI; PADANILAM, BENZY J.; CIUFFO, ALLEN; GUPTA, NIGEL; GALLAGHER, PETER; GOLDNER, BRUCE; HAMMILL, ERIC F.; WOLD, NICOLAS; STEIN, KENNETH; BURKE, MARTIN
Anatomically Designed Quadripolar LV Leads: Introduction: The safety and efficacy of a novel family of quadripolar left ventricular (LV) pacing leads designed to pace from nonapical regions of the LV with low pacing capture thresholds was studied in patients undergoing implantation of a cardiac resynchronization therapy defibrillator (CRT‐D). Methods and Results: Patients receiving a CRT‐D were implanted with 1 of 3 ACUITY X4 leads (Spiral Long, Spiral Short, or Straight), designed to address coronary venous anatomical variability. Electrical performance and LV lead related complications were evaluated 3 and 6 months post implantation, respectively. 764 patients (68 ± 11 years, 66% male) were enrolled; 738 (97%) successfully implanted with an ACUITY X4 lead (Spiral L, n = 239, 31%; Spiral S, n = 281, 37%; Straight, n = 218, 29%). A targeted threshold ≤2.5 V was achieved in 644 (94%) patients. The median threshold from the best proximal electrode was lower than the tip electrode (0.9 V [IQR 0.7, 1.3] vs. 1.3 V [IQR 0.7, 2.5], p< 0.001) on Spiral leads. Irrespective of lead implanted, one of the proximal electrodes was the programmed cathode in most patients. The overall LV complication‐free rate was 98%. LV lead dislodgment occurred in 8 (1%) patients. PNS occurred in 58 (8%) patients, but only 3 (0.4%) patients required surgical intervention. Conclusion: The ACUITY X4 LV leads had low pacing thresholds particularly from proximal electrodes, a high incidence of pacing from the nondistal electrode, and low likelihood of dislodgment or PNS requiring surgical intervention. (ClinicalTrials.gov Identifier: NCT02071173)